2015
DOI: 10.1186/s40468-014-0010-0
|View full text |Cite
|
Sign up to set email alerts
|

Self-assessment as academic community building: a study from a Japanese liberal arts university

Abstract: Student self-assessment has been heralded as a way of increasing student ownership of the learning process, enhancing metacognative awareness of their learning progress as well as promoting learner autonomy. In a university setting, where a major aim is to promote critical thinking and attentiveness to one's responsibility in an academic community, the temptation to implement self-assessment is undeniable. In the liberal arts university context, the activity seems to speak directly to the values and belief sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 25 publications
0
5
0
4
Order By: Relevance
“…Freshman of private university students in Japan also mentioned that the experience they gained from self-assessment has made them determined to work harder to get better scores. Moreover students felt appreciated from the trust given by the instructors and the opportunity to trust in their own judgment as raters (Hale 2015). This has confirmed that self-assessment is more than just an alternative assessing tool since it stimulates a person to reflect on his work, nurtures his learning skills and abilities as well as encourages students to be more responsible of their own learning (Sluijsmans, Dochy & Moerkerke 1999;Nurul Hadani et al 2015).…”
Section: Discussionmentioning
confidence: 65%
“…Freshman of private university students in Japan also mentioned that the experience they gained from self-assessment has made them determined to work harder to get better scores. Moreover students felt appreciated from the trust given by the instructors and the opportunity to trust in their own judgment as raters (Hale 2015). This has confirmed that self-assessment is more than just an alternative assessing tool since it stimulates a person to reflect on his work, nurtures his learning skills and abilities as well as encourages students to be more responsible of their own learning (Sluijsmans, Dochy & Moerkerke 1999;Nurul Hadani et al 2015).…”
Section: Discussionmentioning
confidence: 65%
“…Chen (2014) shows that the independent support of teachers can influence students' motivation level and the degree of learning involvement. Hale (2015) confirms that learners' self-evaluation can cultivate their ability of autonomous learning. Qin (2015) proposes to use corpus to improve students' independent learning ability.…”
Section: Introductionmentioning
confidence: 61%
“…Além disso, a autora menciona que, como qualquer habilidade que é apoiada e aprendida, a acurácia da autoavaliação melhora ao longo do tempo. Hale (2015) acrescenta que estudantes e professores devem usar a mesma ferramenta de avaliação, evitando a impressão de que somente a ferramenta utilizada pelo professor é válida para fins somativos.…”
Section: 2unclassified